2009
DOI: 10.1097/jom.0b013e31819eaac0
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Normal Impairment Factor in Quantifying Avoidable Productivity Loss Because of Poor Health

Abstract: This study demonstrated the utility of the NIF in estimating the level of productivity loss that cannot be regained through health management interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 41 publications
0
16
0
2
Order By: Relevance
“…In our study, 8.5% of the variance in productivity impairment was accounted for by the health risks, while Riedel et al 28 found that 7.8% was accounted for by the health risks. Second, we were able to replicate the amount of productivity impairment that can be accounted for by what Riedel et al 28 have articulated as the "normal impairment factor" (NIF). The NIF is a quantified portion of productivity lost which is not attributable to health risks and provides realistic targets against which one can gauge the amount of productivity loss that might be recaptured with population health management strategies.…”
Section: Discussionmentioning
confidence: 98%
“…In our study, 8.5% of the variance in productivity impairment was accounted for by the health risks, while Riedel et al 28 found that 7.8% was accounted for by the health risks. Second, we were able to replicate the amount of productivity impairment that can be accounted for by what Riedel et al 28 have articulated as the "normal impairment factor" (NIF). The NIF is a quantified portion of productivity lost which is not attributable to health risks and provides realistic targets against which one can gauge the amount of productivity loss that might be recaptured with population health management strategies.…”
Section: Discussionmentioning
confidence: 98%
“…Only back pain was more highly correlated to lost productivity than mental well-being. 27 Although those who are satisfied with their jobs generally consider themselves more productive, perhaps the more interesting of our findings suggests that those people who are not satisfied with their jobs tend to be people who believe that they are performing better than their peers. In particular, the group identifying themselves as not very satisfied with their jobs had the highest percentage identifying themselves as performing higher than their peers (ie, 66.7% in the overperforming stratified presenteeism measure [ Table 2]).…”
mentioning
confidence: 78%
“…Specifically, the productivity loss of employees with the average number of risk factors (about 3 risks) was $5952 per yearthis compared to productivity loss of $1472 per year for employees with no health risks. 27 Using data from the StayWell study, another way to express the monetary relevance of accurate productivity measurement is to equate changes in 1 risk factor to attendant changes in productivity costs. The StayWell research indicates that, on average, a risk factor equates to $1494 in productivity loss.…”
mentioning
confidence: 99%
“…According to Lerner, Rogers and Chang (2003), depression is the highest cause of expense in terms of average productivity loss. Further studies revealed that other psychological problems such as job burnout and stress are associated with higher levels of presenteeism Hemp 2004;Pelletier et al 2004;Riedel et al 2009;Van de Heuvel, Geuskens, Hooftman, Koppes and Van den Bossche 2010). Considering this, we posit our first hypothesis:…”
Section: Introductionmentioning
confidence: 94%